The effects of propolis on performance, carcass and antioxidant status characteristics in quails reared under different stocking density - Arslan, Aslihan Sur; Seven, Pinar Tatli; Yilmaz, Seval; Seven, I. (Eugen Ulmer Gmbh Co, 2014)
The objective of the present study was to investigate the effects of supplementation of an ethanolic extracted of propolis (EEP) to the basal diet on performance, carcass characteristics and antioxidant status in quails under high stocking density. In total, 288 Japanese quails (Coturnix coturnix japonica) were divided into 5 treatment groups, each with four replicates consisting of 8 birds in control groups and 16 birds in other groups. The quails were kept in cages. The available space was 160 and 80 cm(2)/quail in the control and the high stocking density (HS) groups, respectively. The control group (negative control) and HS group (positive control) were fed a basal diet, whereas, the EEP-0.5, EEP-1, EEP-1.5 groups were fed the basal diet supplemented with 0.5, 1.0 and 1.5 g EEP/kg, respectively. At 42 days of age 8 birds were slaughtered and blood was collected. Carcass characteristics and MDA, CAT and GSH contents were determined in blood and tissues. Increased body weight gain, feed intake and improved FCR were found in propolis supplemented quails kept under HS (80 cm(2) /quail) in comparison to the positive control group (HS) in the period 8 to 42 days of life (P < 0.01). Carcass characteristics did not differ significantly between groups (P > 0.05). The catalase (CAT) and reduced glutathione (GSH) c contents of blood were significantly higher in the negative control than in HS and EEP-0.5 groups (p < 0.05). The malondialdehyde (MDA) contents in muscle were significantly lower in the control group than in HS and EEP-0.5 groups (p < 0.05). CAT and GSH contents of muscles were significantly higher in the control group than in HS and EEP-0.5 groups (p < 0.05). The GSH activities of liver were significantly higher in the control group than in HS and EEP-1 groups (p < 0.05). The CAT and GSH activities of blood, muscle and liver, MDA activities of muscle and liver of EEP-1 group were similar to the negative control group. The CAT contents of blood, MDA, CAT and GSH contents of muscle, CAT and GSH contents of liver in EEP-1.5 group were similar to the control group. Results indicate that supplementation of propolis positively affects performance. Propolis supplementation ameliorated the negative effects of high stocking density on lipid peroxidation (MDA, CAT, GSH) in blood, muscle and liver. The present study demonstrated that supplementation of 1 g propolis/kg diet provided the greatest amelioration and showed the highest antioxidant activity. Thus, it could be concluded that propolis can be used as an additive in rations of quails reared under high stocking density.
Einfluss von propolis auf die Leistung, die Schlachtkörperqualität und den antioxidativen Status von Wachteln bei unterschiedlicher Besatzdichte
Keywords: Japanese quail; propolis; stocking density; performance; carcass characteristics; antioxidant status